Importance of methylammonium iodide partial pressure and evaporation onset for the growth of co-evaporated methylammonium lead iodide absorbers - Karl L. Heinze (Nature Portfolio, 2021)
Abstract Vacuum-based co-evaporation promises to bring perovskite solar cells to larger scales, but details of the film formation from the physical vapor phase are still underexplored. In this work, we investigate the growth of methylammonium lead iodide (MAPbI $$_3$$ 3 ) absorbers prepared by co-evaporation of methylammonium iodide (MAI) and lead iodide (PbI $$_2$$ 2 ) using an in situ X-ray diffraction setup. This setup allows us to characterize crystallization and phase evolution of the growing thin film. The total chamber pressure strongly increases during MAI evaporation. We therefore assume the total chamber pressure to be mainly built up by an MAI atmosphere during deposition and use it to control the MAI evaporation. At first, we optimize the MAI to PbI $$_2$$ 2 impingement ratios by varying the MAI pressure at a constant PbI $$_2$$ 2 flux rate. We find a strong dependence of the solar cell device performance on the chamber pressure achieving efficiencies > 14 $$%$$ % in a simple n-i-p structure. On the road to further optimizing the processing conditions we vary the onset time of the PbI $$_2$$ 2 and MAI deposition by delaying the start of the MAI evaporation by t = 0/8/16 min. This way, PbI $$_2$$ 2 nucleates as a seed layer with a thickness of up to approximately 20 nm during this initial stage. Device performance benefits from these PbI $$_2$$ 2 seed layers, which also induce strong preferential thin film orientation as evidenced by grazing incidence wide angle X-ray scattering (GIWAXS) measurements. Our insights into the growth of MAPbI $$_3$$ 3 thin films from the physical vapor phase help to understand the film formation mechanisms and contribute to the further development of MAPbI $$_3$$ 3 and related perovskite absorbers.